Hubungan Konsep Diri Negatif dengan Hambatan dalam Interaksi Sosial Antar Teman Sebaya Siswa SMA DARUL HIKAM - Fauzan, Fajar Rifki; Muhammad Restu Aditya; Failasuf Faiq (Institut Agama Islam Negeri Curup, 2025)
This study aims to determine the relationship between negative self-concept and negative social interaction among students at SMA Darul Hikam through the independent variable (X) and the dependent variable (Y). This research employs a quantitative approach with a descriptive correlation method. The data were obtained from students at SMA Darul Hikam, with data collection conducted through observations and questionnaires distributed to the research sample. The results indicate a significant positive relationship between negative self-concept and negative social interaction, with a correlation coefficient of 0.529 and a significance level of p = 0.000 (p < 0.05). These findings suggest that the higher a student's negative self-concept, the greater their tendency to engage in negative social interactions. Conversely, students with lower levels of negative self-concept tend to exhibit more positive social interactions. This study supports the hypothesis that self-concept plays a crucial role in shaping the quality of students' social interactions.